Acute colonic pseudo-obstruction in a child taking trihexyphenidyl for drooling: Prescribers beware. Issue 6 (June 2015) - Begbie, F.; Walker, G.; Kubba, H.; Sabharwal, A.
Abstract: Colonic pseudo-obstruction (Ogilvie's Syndrome) in children is relatively uncommon. We report an unusual case of colonic pseudo-obstruction in an 8-year-old child with cerebral palsy and long-term hypomotility issues being treated for drooling with the anticholinergic medication trihexyphenidyl. He presented as an emergency with severe abdominal distension, abdominal tenderness and vomiting. An emergency laparotomy revealed colonic dilatation and a defunctioning ileostomy was created. To our knowledge, this is the first case reporting colonic pseudo-obstruction as a possible complication of treatment with trihexyphenidyl. We suggest prescribers should exercise caution when prescribing trihexyphenidyl in patients with long-term intestinal hypomotility issues.